2022
DOI: 10.3390/molecules27072266
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and In Vivo Study of Some Novel 3,4,5-Trimethoxybenzylidene-hydrazinecarbothioamides and Thiadiazoles as Anti-Apoptotic Caspase-3 Inhibitors

Abstract: The present study aims to discover novel derivatives as antiapoptotic agents and their protective effects against renal ischemia/reperfusion. Therefore, a series of new thiadiazole analogues 2a–g was designed and synthesized through cyclization of the corresponding opened hydrazinecarbothioamides 1a–g, followed by confirmation of the structure via spectroscopic tools (NMR, IR and mass spectra) and elemental analyses. The antiapoptotic activity showed alongside decreasing of tissue damage induced by I/R in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…Importantly, we indicated that the selected concentrations of these compounds did not have a significant effect on caspase activity, and consequently, the induction of RPTEC apoptosis. Furthermore, Mostafa et al, (2022) demonstrated that some thiadiazole derivatives had anti-apoptotic properties in the kidneys of rats through caspase inhibition [ 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, we indicated that the selected concentrations of these compounds did not have a significant effect on caspase activity, and consequently, the induction of RPTEC apoptosis. Furthermore, Mostafa et al, (2022) demonstrated that some thiadiazole derivatives had anti-apoptotic properties in the kidneys of rats through caspase inhibition [ 84 ].…”
Section: Discussionmentioning
confidence: 99%